The endogeneity of money and the eurosystem - Otto Steiger (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
The endogenous theory of money, developed by Basil Moore, argues that the supply of central bank money in modern economies is not under the control of the central bank. According to this view, a central bank typically supplies cash reserves automatically on demand at its minimum lending rate, resulting in a clearly horizontal money supply function. While the paper agrees with Moore that the supply of central bank money cannot be determined exogenously by the central bank, it wonders whether the supply is determined completely by the demand of the commercial banks. The paper suggests that the central bank has some exogenous power to control the quantity of its supply by rationing. More importantly, the central bank is forced to do so! The central bank cannot not merely exist as an automat responding to the wishes of the commercial banks. Part I discusses the cause why the central bank has to restrict its supply, while part II demonstrates how the supply of central bank money can be controlled by looking at the monetary policy operations of the Eurosystem. In accordance with this analysis, the paper offers a modified horizontal or “staircase” supply function of central bank money.
Keywords: E51; E58; 330